Spontaneous Orientation Polarization of Anisotropic Equivalent Dipoles Harnessed by Entropy Engineering for Ultra-Thin Electromagnetic Wave Absorber - Wang, Honghan; Xiao, Xinyu; Zhai, Shangru; Xue, Chuang; Zheng, Guangping; Zhang, Deqing; Che, Renchao; Cheng, Junye (Nano-Micro Letters, 2024)
The synthesis of carbon supporter/nanoscale high-entropy alloys (HEAs) electromagnetic response composites by carbothermal shock method has been identified as an advanced strategy for the collaborative competition engineering of conductive/dielectric genes. Electron migration modes within HEAs as manipulated by the electronegativity, valence electron configurations and molar proportions of constituent elements determine the steady state and efficiency of equivalent dipoles. Herein, enlightened by skin-like effect, a reformative carbothermal shock method using carbonized cellulose paper (CCP) as carbon supporter is used to preserve the oxygen-containing functional groups (O·) of carbonized cellulose fibers (CCF). Nucleation of HEAs and construction of emblematic shell-core CCF/HEAs heterointerfaces are inextricably linked to carbon metabolism induced by O·. Meanwhile, the electron migration mode of switchable electron-rich sites promotes the orientation polarization of anisotropic equivalent dipoles. By virtue of the reinforcement strategy, CCP/HEAs composite prepared by 35% molar ratio of Mn element (CCP/HEAs-Mn2.15) achieves efficient electromagnetic wave (EMW) absorption of − 51.35 dB at an ultra-thin thickness of 1.03 mm. The mechanisms of the resulting dielectric properties of HEAs-based EMW absorbing materials are elucidated by combining theoretical calculations with experimental characterizations, which provide theoretical bases and feasible strategies for the simulation and practical application of electromagnetic functional devices (e.g., ultra-wideband bandpass filter). Highlights: 1 The strengthening mechanism of spontaneous orientation polarization of anisotropic equivalent dipoles within high-entropy alloys (HEAs) is proposed for enhancing dielectric attenuation of HEAs. 2 The source of carbon supporter is expanded to the biomass category, which can construct the shell-core heterointerfaces with HEAs by means of a reformative carbothermal shock method. 3 The sample carbonized cellulose paper/HEAs-Mn2.15 achieves efficient electromagnetic wave absorption of -51.35 dB at an ultra-thin thickness of 1.03 mm. 4 This work combines theoretical calculations and electromagnetic simulations to propose feasible strategies for the design and application of electromagnetic functional devices such as ultra-wideband bandpass filter.